School feeding or general food distribution? Quasi-experimental evidence on the educational impacts of emergency food assistance during conflict in Mali - Aurino, Elisabetta; Tranchant, Jean-Pierre; Diallo, Amadou Sekou; Gelli, Aulo (Informa UK Limited, 2019)
This study relies on a unique precrisis baseline and five-year follow-up to investigate the effects of emergency school feeding and generalised food distribution (GFD) on children’s schooling during conflict in Mali. It estimates programme impact on child enrolment, absenteeism, and attainment by using a difference in differences weighted estimator. School feeding led to increases in enrolment by 10 percentage points and to around an additional half-year of completed schooling. Attendance among boys in households receiving GFD, however, declined by about 20 per cent relative to the comparison group. Disaggregating by conflict intensity showed that receipt of any food assistance led to a rise in enrolment mostly in high-intensity conflict areas and that the negative effects of GFD on attendance were also concentrated in the most affected areas. School feeding mostly raised attainment among children in areas not in the immediate vicinity of conflict. Programme receipt triggered adjustments in child labour. School feeding led to lower participation and time spent in work among girls, while GFD raised children’s labour, particularly among boys. The educational implications of food assistance should be considered in planning humanitarian responses to bridge the gap between emergency assistance and development by promoting children’s education.